2016
DOI: 10.1002/icd.2013
|View full text |Cite
|
Sign up to set email alerts
|

Parental alcohol use, parenting, and child on‐time development

Abstract: This study examined whether parental alcohol use in adolescence, adulthood, and, for mothers, during pregnancy was related to their young children's functioning in terms of their on-time development as indicated by the number of developmental areas in which children experienced delay. Observed parenting practices and family socioeconomic status were tested as potential explanatory mechanisms of these links. Data came from the surveys and videotaped observations of a community sample of 123 biological parents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 75 publications
(113 reference statements)
2
9
0
Order By: Relevance
“…Few studies have considered relations between both mothers' and fathers' drinking on children's development and sex-/gender-related comparisons are needed (Guttmannova et al, 2016). Of available findings, some have indicated that men's PD compromises children's development to a greater degree (Guttmannova et al, 2016;Keller et al, 2008), including in relation to sleep problems (Kelly & El-Sheikh, 2016). Consistent with these findings, the current results indicate that fathers' PD was directly related to change in two of the four examined sleep parameters (while controlling for mothers' PD), and all four tested interactions between fathers' PD and SES were significant.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have considered relations between both mothers' and fathers' drinking on children's development and sex-/gender-related comparisons are needed (Guttmannova et al, 2016). Of available findings, some have indicated that men's PD compromises children's development to a greater degree (Guttmannova et al, 2016;Keller et al, 2008), including in relation to sleep problems (Kelly & El-Sheikh, 2016). Consistent with these findings, the current results indicate that fathers' PD was directly related to change in two of the four examined sleep parameters (while controlling for mothers' PD), and all four tested interactions between fathers' PD and SES were significant.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that family environment plays a crucial role for the development of the child's language skills [29][30][31][32], as well as social skills [31,[33][34][35][36]. However, little is known about parent-child talk in the perspective of the development of children's pragmatic elements of language, such as the ability to comprehend figurative speech, especially irony [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Children expose to parental smoking are at increased risk of increased C-reactive protein in adulthood, which may contribute to long-term effects on low-grade inflammation [49]. Regular alcohol consumption by the father is related to low family SES, which predicts less-skilled parenting practices and children’s developmental delay in children [50].…”
Section: Discussionmentioning
confidence: 99%